The Economic Growth on Regional Financial Independence (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the partial and simultaneous influence of local revenue, general allocation funds, and economic growth on regional financial independence in the district and city regional governments in West Java Province during the 2013-2015 period. The research method used in this study is an explanatory method. The results of the study show that partially and simultaneously local revenue, general allocation funds, and economic growth affect regional financial independence